Functional Three-Dimensional Porous Conductive Polymer Hydrogels for Sensitive Electrochemiluminescence in Situ Detection of H2O2 Released from Live Cells - Jiang, Xinya; Wang, Huijun; Yuan, Ruo; Chai, Yaqin (Analytical chemistry (Washington), 2018)
Reliable and sensitive in situ detection of molecules released from live cells attracts tremendous research interest, as it shows significance in pathological and physiological investigation. In the present work, a novel electrochemiluminescent (ECL) luminophore, N-(aminobutyl)-N-(ethylisoluminol)-functionalized Ag nanoparticles modified three-dimensional (3D) polyaniline–phytic acid conducting hydrogel (ABEI–Ag@PAni–PA), is synthesized to adhere cells for in situ sensitive ECL detection of hydrogen peroxide (H2O2) released from live cells. The obtained 3D nanostructured ABEI–Ag@PAni–PA conducting hydrogels synergize the advantages of a conducting hydrogel and a nanoparticle catalyst, in which the PAni–PA conducting hydrogels benefit the cell adhesion and high loading density of the ABEI–Ag luminescent material due to their good biocompatibility, porous structure, and 3D continuous framework. Importantly, compared with the traditional procedure for detection of H2O2 released from cells in solution, adhesion of cells on ABEI–Ag@PAni–PA conducting hydrogels provides a short diffusion distance to reaction sites for H2O2, thus realizing sensitive in situ monitoring of H2O2 released from cells under drug stimulation. With good biocompatibility, high sensitivity, and easy preparation, the ECL biosensor based on ABEI–Ag@PAni–PA conducting hydrogels can be expanded to detect other molecules released from cells, which may facilitate the investigation of pathology and physiology.